Musical intervention with a predominance of low frequencies: gender- and age-related psychophysiological effects - Тарасова, Катерина; Тимощенко, Наталія (Psychosomatic Medicine and General Practice, 2025)
Relevance. In modern psychophysiology, there is a growing interest in studying the effects of musical stimuli on the human condition. Particular attention is given to low-frequency sounds, which are capable of inducing deep bodily and emotional reactions, facilitating relaxation or, conversely, increasing arousal. The bassoon – a wind instrument with a rich, deep timbre in the low register – remains a rare subject of psychophysiological research, despite its pronounced acoustic and emotional characteristics. Unlike synthetic or abstractly generated low-frequency sounds, the sound of the bassoon is natural, musically structured, and rich in harmonics, making its influence distinctive. Gender and age differences in the perception of music are acknowledged: women are generally more emotionally sensitive to musical stimuli than men, and auditory processing, particularly of low-frequency sounds, changes with age. Wartime conditions and the associated increase in anxiety levels create a need to investigate the impact of musical characteristics on various socio-biological groups, with the perspective of applying this knowledge in music therapy tailored to gender and age – a scientifically sound and timely approach. Objective. To identify gender- and age-related features of the impact of a musical intervention with predominantly low-frequency sounds on anxiety levels, in order to enhance the effectiveness of music therapy in the context of emotional regulation. Materials and methods. The audio material consisted of recordings of bassoon partitas predominantly in the low-frequency range. Heart rate was measured using a tonometer or pulse oximeter. Situational and trait anxiety levels were assessed using the Spielberger–Khanin Anxiety Inventory. Results and discussion. The study involved 96 volunteers: 50 younger individuals (18 men aged 28,7±7,2 and 32 women aged 23,7±6.5 years) and 46 older individuals (16 men aged 53,3±7,6 and 30 women aged 56,8±8,8 years). Baseline levels of situational and trait anxiety were generally medium or high across all groups, with no statistically significant differences. Among young women, whose baseline heart rate was relatively high (94.1±12.7 bpm), listening to the musical piece resulted in a significant decrease of 12,1±3,36 bpm (p < 0.05). The reduction in situational anxiety was most effective in individuals of either gender with a high initial anxiety level, particularly in the younger age group. Among older women with low or medium levels of situational anxiety, the proposed musical piece occasionally triggered negative emotions and led to an increase in both situational and trait anxiety, which should be considered when applying music therapy. Conclusions. Listening to a musical piece dominated by low frequencies led to changes in heart rate and anxiety levels (both situational and trait) in participants of different genders and ages. These changes varied in magnitude and direction depending on the initial levels of the measured indicators. Keywords: music intervention, low-frequency sounds, bassoon, situational anxiety, trait anxiety